Impaired Coronary Microvascular Function and Its Association with Disease Duration and Inflammation in Patients with Psoriasis. Issue 8 (12th March 2013) - Gullu, Hakan; Caliskan, Mustafa; Dursun, Recep; Ciftci, Ozgur; Guven, Aytekin; Muderrisoglu, Haldun
<x xml:space="preserve">Abstract</x> Subjects Thirty‐six patients with psoriasis and 56 healthy volunteers were included in this study. Methods Echocardiographic examination included transmitral peak flow velocities of the early phase (E) and late phase (A) of the mitral inflow, left ventricular myocardial velocity measurements, and coronary flow reserve (CFR) measurement. Results Baseline coronary diastolic peak flow velocity (DPFV) of left anterior descending artery (LAD) was significantly higher in the psoriasis group. However, hyperemic DPFV was slightly lower and CFR (2.19 ± 0.39 vs. 2.60 ± 0.31, P < 0.0001) was significantly lower in the psoriasis group than in the control group. CFR was significantly and inversely correlated with disease duration, Psoriasis Area and Severity Index (PASI) score, and hsCRP. Conclusion CFR is decreased in patients with psoriasis, and it correlates to disease duration, PASI score, and inflammation.